Um percurso pelas configurações do corpo de personagens travestis em narrativas brasileiras do século xx: 1960-1980 - Fernandes , Carlos Eduardo Albuquerque (2016)
The present work presents the construction of a critical analysis of travestite protagonists in Brazilian literary narratives of the 20th century, focusing at long narratives produced between the sixties and eighties. The selected narratives are the following: Uma mulher diferente, by Cassandra Rios (1965); “O milagre”, by Roberto Feire (1978); O Travesti (1980), by Adelaide Carraro; O fantasma travesti, by Sylvia Orthof, (1988). Along the research, we constructed a diacronic and critical perspective on the selected literary corpus, presenting discussions on the configuration of the body as a relevant aspect to the construction of the travestite character as well as the social, cultural and historical transformations that marked this minority existence among constant attempts to normatize gender and sex. When the social context brings up changes in terms of body, alterity and gender perceptions, literature, being part and marked by social discourses, gets impregnated of such subjective constructions, bringing them to paper. The protagonists in the analyzed narratives, “beings on paper” materializing the body that suffers constraint, provokes us to interpret their social and subjective construction. Our theoretical fundaments were: (a) the concept of the travestite and travestility, based on etnographic work on the experience of Brazilian travestite subjects by Benedetti (2005), Kulick (2008), Oliveira (1994), Silva, (2007) and Pelúcio (2009). (b) the discussion of the body as a possibility of subversion and domination, according to Foucault (2014, 2013), Preciado (2015) and Butler (2010, 2013); (c) literary studies which take the character as a narrative element, and gender as well as sexuallity questions, in authors such as Candido (2007), Barcellos (2006), Xavier (2007). At the end of our research we confirmed that there is a peculiar way identified in literary texts of presenting and constructing such travestite ficcional subjects along the 20th century, what is verified in different contexts and narrative genres, in terms of thematic and linguistic choices, indicating that the protagonists have the potential to break with or reinforce power structures, what we indicate and discuss along the chapters.